一、35.设函数f(x+3)=x(x+3)则f(x)=

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/10 17:37:51
一、35.设函数f(x+3)=x(x+3)则f(x)=
xN0_c M3Xlv+ Q< A *U >-١Bb󙧱i ׳ګ& .B [GџFiG`` cN'- VP4uxGai}`OX!N_YpӾtzZ@3ߋ-s|K< $.Тnz AD&:}O 96 Wg5CPUE3k@~>/,vt

一、35.设函数f(x+3)=x(x+3)则f(x)=
一、35.设函数f(x+3)=x(x+3)则f(x)=

一、35.设函数f(x+3)=x(x+3)则f(x)=
f(x+3)=x(x+3)=(x+3-3)(x+3),把式子中的x+3换成x得到f(x)=x(x-3)

令x+3=t,则x=t-3,原式变为:f(t)=(t-3)t
所以f(x)=x(x-3)

令 x+3=t 则 f(t)=(t-3)t
即 f(x)= x(x-3)

令X=x+3;函数就为f(X)=X(X-3) 再把X换为x
就有f(x)=x(x-3)

f(x+3)=x(x+3)=(x+3-3)(x+3)
f(x)=(x-3)*x=x(x-3)